REMOVAL OF IRON IMPURITIES FROM FLY AND BOTTOM ASH BY NEODYMIUM MAGNET - แปงหลวง, กฤษณะ; เพชรวงษ์, ภูมิมนทร์; จิราสิต, ฟองจันทร์; ทองสุก, วิริยะ; ศิริลักษณ์, ศิวโรฒน์ (RMUTL Engineering Journal, 2016)
In this research, fly and bottom ash samples from Mae Moh power plant, Lampang, Thailand were reported by XRF. The %Fe element in samples was nearly 10%. The neodymium permanent magnet was used to remove iron impurities in wet process. The results showed reduction in fly and bottom ash to 6.02%Fe at magnetic flux density (B) = 3573 G and 5.23%Fe at B = 3705 G, respectively. The maximum %Fe recoveries were 90% and 79% in fly ash and bottom ash, respectively.